2005
DOI: 10.1149/1.1931447
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed-Conduction Model for the Oxidation of Stainless Steel in a High-Temperature Electrolyte

Abstract: The oxide films formed on AISI 316L͑NG͒ in the temperature range 150-300°C have been characterized by impedance spectroscopy and ex situ analysis using Auger electron spectroscopy. Relatively thick films containing a high concentration of mobile defects form on stainless steel in a high-temperature borate electrolyte, but their impedance response is most probably controlled by the properties of a thin barrier sublayer. The ability of the mixed conduction model for passive films to reproduce the experimental im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 56 publications
4
42
2
Order By: Relevance
“…According to the PDM and the MCM the transport of oxygen vacancies in the oxide is governed by both diffusion and migration [22][23][24][25]: pores of the outer layer and x = L at the alloy/barrier layer interface, L being the barrier layer thickness, gives the concentration profile of oxygen vacancies in the barrier layer:…”
Section: Alloy=barrier Layer Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…According to the PDM and the MCM the transport of oxygen vacancies in the oxide is governed by both diffusion and migration [22][23][24][25]: pores of the outer layer and x = L at the alloy/barrier layer interface, L being the barrier layer thickness, gives the concentration profile of oxygen vacancies in the barrier layer:…”
Section: Alloy=barrier Layer Interfacementioning
confidence: 99%
“…On the other hand, some of us have adapted the mixed-conduction model (MCM) for oxide films [24,25] to quantitatively describe the in situ impedance data for several Zircaloy 2-type alloys in simulated boiling water reactor (BWR) coolant at 300°C [20]. As a consequence, several important kinetic and transport parameters of the growing oxide have been estimated.…”
Section: Introductionmentioning
confidence: 99%
“…The dissolution process of chromium oxides in the passive film was discussed and it was believed that this process led to the formation of duplex structure of passive film, namely the rich-chromium inner layer and poor-chromium outer layer. Bojinov [8,9] put forward a new model of passive film on Fe-Cr alloys through the measurement of contact resistance, photoelectrochemical method and electrochemical impedance spectroscopy (EIS). He believed that this kind of passive film was composed of one main film and two highly defect interface regions beside it.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of the mixed-conduction model ͑MCM͒ for passive films [5][6][7][8] to reproduce the experimental impedance data in both configurations has been verified. The MCM is at the conceptual level quite similar to the point defect model ͑PDM͒ developed by Zhang and Macdonald 9,10 and Macdonald 11,12 over the last few decades.…”
mentioning
confidence: 78%
“…The fact that the impedance of this film does not change significantly with temperature suggested that its electrical and electrochemical properties remain qualitatively unaltered in the entire studied temperature interval. In general, the impedance and surface analytical results reported earlier by some of the authors 5 indicate that regardless of the fact that comparatively thick oxide layers are formed especially at temperatures exceeding 200°C, the kinetics of the overall film growth and corrosion process is governed by a thin barrier layer. In that respect, this quantitative treatment based on a conceptual model consisting of a very thin barrier layer adjacent to the alloy substrate and a much thicker layer growing by dissolution-redeposition has been found to be in full quantitative agreement with the electrochemical impedance data measured after short oxidation times.…”
mentioning
confidence: 81%